2017
DOI: 10.21037/jtd.2017.07.35
|View full text |Cite
|
Sign up to set email alerts
|

Patient reported outcomes following video assisted thoracoscopic (VATS) resection or stereotactic ablative body radiotherapy (SABR) for treatment of non-small cell lung cancer: protocol for an observational pilot study (LiLAC)

Abstract: Background: Lung cancer is increasingly a disease of the elderly and frail population with a median age of 70 years at diagnosis. Therefore, consideration of the impact of interventions on health-related quality of life (HRQOL) and not only absolute survival is especially important. For non-small cell lung cancer (NSCLC), video-assisted thoracoscopic surgery (VATS) has been gaining popularity over the last few decades, replacing traditional open lobectomies. For high-risk patients who are not deemed suitable f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…The most effective treatment options for curative lung cancer are video assisted thoracoscopic (VATS) resection or stereotactic ablative body radiotherapy (SABR) for patients unfit for surger. The treatment effectiveness is evaluated on survival data (1,2) and presently there is little information about the effects of these treatments on patients' quality of life (QOL) (3,4). About 44% of patients diagnosed with lung cancer are aged 75 and over (5) and commonly have multiple comorbidities with 54% presenting with three or more (6) reducing their eligibility for surgery (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…The most effective treatment options for curative lung cancer are video assisted thoracoscopic (VATS) resection or stereotactic ablative body radiotherapy (SABR) for patients unfit for surger. The treatment effectiveness is evaluated on survival data (1,2) and presently there is little information about the effects of these treatments on patients' quality of life (QOL) (3,4). About 44% of patients diagnosed with lung cancer are aged 75 and over (5) and commonly have multiple comorbidities with 54% presenting with three or more (6) reducing their eligibility for surgery (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…This study assesses the utility of a patient reported measure of decision making confidence carried out as part of the Life after Lung Cancer (LiLAC) study [4]. LiLAC used validated Patient-reported outcome measures (PROMs) to describe the trajectory of Quality of Life (QoL) following VATS or SABR treatment.…”
Section: Design and Samplementioning
confidence: 99%
“…The most effective treatment options for curative lung cancer are video assisted thoracoscopic (VATS) resection or stereotactic ablative body radiotherapy (SABR) for patients unfit for surgery. The treatment effectiveness is evaluated on survival data [ 1 , 2 ] and presently there is little information about the effects of these treatments on patients’ quality of life (QoL) [ 3 , 4 ]. About 44% of patients diagnosed with lung cancer are aged 75 and over [ 5 ] and commonly have multiple comorbidities with 54% presenting with three or more [ 6 ] reducing their eligibility for surgery [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] Patient and clinician prior preferences between surgical and SABR treatments and the need for involvement in decisions have been challenges for NSCLC clinical trials. [5,6] When clinical outcomes after surgery or SABR are not easily comparable, it is vital to involve patients in decision-making, discussing the reasons for pre-existing patient, and clinician, preferences, can support the shared decision making process, and may improve satisfaction. [7] This systematic review critically evaluates studies of patient and clinician preferences for treatment of early stage NSCLC to explore:…”
Section: Introductionmentioning
confidence: 99%